The Effect of Problem Based Learning (PBM) to the Basic Physics II Achievement In terms of scientific methodology and attitude of Physics Students Scientific-Education Program, State University of Malang - Eddy Supramono (Jurnal Pendidikan Sains, 2013)
Pengaruh Pembelajaran Berbasis Masalah (PBM) terhadap Prestasi Belajar Fisika Dasar II Ditinjau dari Kerja Ilmiah dan Sikap Ilmiah Mahasiswa Abstract: The Lecture of Basic Physics theory tend to be informative, lecturers tend to resolve existing material on the syllabus, consequently any misunderstanding about the student problem solving in physics. This study aims to examine differences in student achievement in the application of PBM models in terms of scientific work and scientific attitude. This research uses research Quasy Experimentation (semi-experimental) with a factorial design that uses two factors and each factor using two categories. The research population is the entire second semester students, forces from 2011 to 2012 as many as 6 classes The research sample taken as many as two classes each class comprised 36 students with purposive sampling. Achievement test instruments in the form of multiple choice questions as many as 25 items that have been tested validity, using the 87 student class of 2010 and 2011 as respondents. Reliability of the instrument sought to use the KR 20. Hypothesis testing using ANOVA statistical Two Line. The results show differences in performance of high-class scientific experiment with the controls but not significantly. There are differences in student achievement low scientific work significantly between the experimental class with the conventional. There are no differences in student achievement between the high scientific attitude with conventional experimental class and also no difference in student achievement are low scientific attitude between the experimental class with the conventional material-Geometric Optics. Key words: PBM, achievements, scientific work, scientific attitudeAbstrak: Kuliah teori Fisika Dasar cenderung berupa informasi, dosen cenderung menuntaskan materi yang ada pada silabi, akibatnya adanya pemahaman yang keliru pada mahasiswa tentang pemecahan masalah dalam fisika. Penelitian ini bertujuan menguji perbedaan prestasi belajar mahasiswa pada penerapan model PBM ditinjau dari kerja ilmiah dan sikap ilmiah. Penelitian ini menggunakan jenis penelitian Quasy Experimentation (semi eksperimen) dengan desain faktorial yang menggunakan dua faktor dan masing-masing faktor menggunakan dua katagori. Populasi penelitian yang digunakan adalah seluruh mahasiswa semester 2, angkatan 2011-2012 sebanyak 6 kelas. Sampel penelitian yang diambil sebanyak 2 kelas yang setiap kelasnya terdiri 36 mahasiswa secara purposive sampling. Instrumen tes prestasi berupa soal pilihan ganda sebanyak 25 butir soal yang telah diuji validitasnya, menggunakan 87 mahasiswa angkatan 2010 dan 2011 sebagai responden. Reliabilitas instrumen dicari dengan menggunakan KR 20. Uji hipotesis menggunakan statistik Anava Dua Jalur. Hasil penelitian menunjukkan adanya perbedaan prestasi kerja ilmiah tinggi kelas eksperimen dengan kontrol tetapi tidak signifikan. Ada perbedaan prestasi belajar mahasiswa kerja ilmiah rendah yang signifikan antara kelas eksperimen dengan konvensional. Tidak terdapat perbedaan prestasi belajar mahasiswa sikap ilmiah tinggi antara kelas eksperimen dengan konvensional dan juga tidak terdapat perbedaanprestasi belajar mahasiswa sikap ilmiah rendah antara kelas eksperimen dengan konvensional pada materi Optika-Geometrik.Kata kunci: PBM, prestasi, kerja ilmiah, sikap ilmiah